The Influence of Spelling on the Pronunciation of English as a Foreign Language as Made by Iraqi EFL Learners at the University Level : A Descriptive Stud - Inst.Furqan Abdul-Ridha Kareem Altaie, AbdulRidha (Journal of College of Education, 2022)
Abstract      The main problem of this research paper  is the influence of spelling on pronunciation . Students  of English find difficulties in pronouncing certain  words from  written text . In Arabic, students can easily pronounce words by just looking at them . In English, there are some words which are spelt with different ways , but they have the same pronunciation. For example, the words (rain) , (rein ) and (reign) , they pronounce in the same way / reɪn/  for the learners who do not mastery pronunciation in the right way , it is difficult to pronounce and they pronounce each word by looking at its spelling . This means that they mispronounced them , because they do not know the exact relationship between sound and spelling .
Keywords: Spelling, pronunciation, Iraqi EFL learners